Pengaruh Keberhasilan Diri dan Toleransi akan Risiko Terhadap Motivasi Berwirausaha pada Mahasiswa Fakultas Bisnis di Jakarta - Cindy Metta Saputra; Basuki Toto Rahmanto (UNIVERSITAS KALBIS, 2022)
This study was conducted to analyze whether self-efficacy motivation and risk tolerance affect students' desire to become entrepreneurs. The research population is students of the Faculty of Business from universities in DKI Jakarta and the sample obtained is 125 respondents. The sampling technique used in this research is accidental sampling. The analytical method used is multiple linear regression. The research data were analyzed using Eviews 9. The results showed that self-efficacy and risk tolerance had a positive influence on entrepreneurial motivation for students at the Faculty of Business in Jakarta